EVALUATION OF THE DEVELOPMENT OF MOTOR SKILLS OF CHILDREN AT RURAL SCHOOLS IN RIO VERDE - GO - Jesus, Jovair Batista de; Silva, Jesiel Souza; Ditomaso, Aline [UNESP]; Vieira, Andreza Alves (Univ Federal Mato Grosso Sul, 2023)
This work aims to evaluate the development of motor skills of children from rural schools in the city of Rio Verde - GO. This is an exploratory field research carried out with 25 children between 9 and 10 years old, who have never lived in the city. The Test of Gross Motor Development -TGMD-2 by Ulrich (2000) was used, which, from two sub-tests, assesses the control of locomotion and handling of objects. Quantitative data analysis revealed that children who live and study in rural areas have development classified as AVERAGE. The analysis of the Gross Motor Development Quotient - QDMG showed that the development of boys is superior to that presented by girls. As for the age-related motor development profile, both genders are above the expected average for their age, which may be related to the quality of bodily experiences lived in rural areas.
Keywords: Motor Development; Motor Skills; TGMD-2 Assessment Protocol e Rural Schools